Peran Bagian Keuangan Dan BMN Dalam Mendukung Operasional Di Balai Besar Wilayah Sungai Ciliwung Cisadane - Lestari, Sri; Chusnah, Chusnah; Ridwan, M.; Asman, Asman; Nasution, Chodijah; Azara, Ekta (Gapenas Publisher, 2022)
This community service aims to analyze the financial section and the management of State-Owned Goods (BMN) in supporting the operations of the Ciliwung Cisadane River Basin Organization (BBWS). Identifying the challenges faced in financial management and State-Owned Goods (BMN) management. Providing recommendations to improve the efficiency and effectiveness of financial management and optimize the use of state assets (BMN) to support the BBWS's tasks in water resource management. The method used is a qualitative approach, including in-depth interviews conducted with finance department employees, BMN managers, and relevant parties at BBWS Ciliwung Cisadane, direct observation of the financial and asset management processes in the BBWS work environment, and document analysis, including financial reports, BMN inventory documents, and relevant regulations. The purpose of this service is to assist in the smooth allocation of budgets, management of expenditures, and financial reporting. So that the implementation of operational activities complies with the applicable regulations. Meanwhile, the management of state assets contributes to the effectiveness of asset utilization, from planning, procurement, to maintenance. Some of the challenges faced include, among others, the limited availability of competent human resources, lack of integration in information systems, and administrative hurdles that slow down the financial and BMN management processes.